Creatine and physical resistance exercises: positive effects and changes in the years: an integrative review - Limaverde Gomes, Isabela; Pinheiro Pereira , Camila; Nogueira Bezerra, Alane; Carolina Amancio, Livia; Pinheiro Cavalcante, Karla; Pereira Aguiar, Larissa; Pereira, Bruno Barros; Henrique Bernardino De Freitas, Pedro; Pereira Souza, Gustavo; Teixeira Terceiro Paim, Raquel (Seven Editora, 2023)
A supplement widely used in resistance training is creatine, which is composed of three amino acids (arginine, glycine, and methionine). It is found primarily in skeletal muscle (95%) and plays an important role in the rapid supply of energy during muscle contraction via the ATP-CP system. Because of this, in this study, an integrative literature review was carried out, to understand the positive effects and renal changes of creatine in physical exercises. The research was carried out between September 2021 and May 2022, with searches in PubMed and Scielo databases. The following descriptors from the DeCS (descriptors in health science created by BIREME) and MESH (medical subject headings) were used: "creatine supplementation", "dose-dependent creatine", "creatine", "Creatine Supplementation and Exercise Training". Most studies have shown that creatine supplementation (CR) is important for resistance training and muscle performance and is an effective resource in increasing energy, as creatine is involved in one of the metabolic energy delivery systems, in which Adenosine bisphosphonates (ADP) are enzymatically linked to phosphocreatine (CP) to regenerate adenosine triphosphate (ATP), the main energy currency. After creatine supplementation, there is more CR in the muscles, which favors an increase in energy supply through ATP resynthesis. DOI: https://doi.org/10.56238/devopinterscie-128